PENGEMBANGAN MULTIMEDIA INTERAKTIF MATERI MENCIPTAKAN PUISI MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP - Faizatul Fakhriyah; Bachtiar Sjaiful Bachri; Utari Dewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This research was based on the needs of students in the subject of poetry creation in eighth Poetry writing instruction for eighth-grade junior high school students continues to face challenges due to the predominance of textbook-based learning and lecture-centered teaching, which have not adequately facilitated students’ active engagement and have consequently limited learning outcomes. This study aimed to analyze the feasibility and effectiveness of interactive multimedia in improving students’ learning outcomes in poetry writing. The study employed the Lee and Owens development model, consisting of the analysis, design, development, implementation, and evaluation stages. The product developed was interactive multimedia using Construct 2, which was validated by subject matter experts, media experts, instructional design experts, and supporting material experts, and subsequently tested with eighth-grade students at SMP Negeri 61 Surabaya. Data were analyzed using validity, reliability, homogeneity, hypothesis, and effect size tests. The findings indicated that the interactive multimedia was classified as highly feasible based on expert validation and students’ responses and was proven effective in improving learning outcomes, as evidenced by a significant difference between the experimental and control groups with a moderate effect size. The novelty of this study lies in the development of interactive multimedia that integrates instructional content, examples, sequential practice activities, immediate feedback, and assessment into a single platform to support the creative process of poetry writing. These findings suggest that interactive multimedia can serve as an alternative instructional medium for Indonesian language learning by promoting more active, meaningful, and learning-oriented classroom experiences. ABSTRAK Pembelajaran menciptakan puisi di kelas VIII SMP masih menghadapi kendala karena dominannya penggunaan buku ajar dan metode ceramah yang kurang mampu memfasilitasi keterlibatan aktif peserta didik sehingga hasil belajar belum optimal. Penelitian ini bertujuan menganalisis kelayakan dan keefektifan multimedia interaktif untuk meningkatkan hasil belajar peserta didik pada materi menciptakan puisi. Penelitian menggunakan model pengembangan Lee and Owens yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Produk yang dikembangkan berupa multimedia interaktif berbasis Construct 2 yang divalidasi oleh ahli materi, ahli media, ahli desain pembelajaran, ahli bahan penyerta, serta diuji kepada peserta didik kelas VIII SMP Negeri 61 Surabaya. Analisis data dilakukan melalui uji validitas, reliabilitas, homogenitas, uji hipotesis, dan effect size. Hasil penelitian menunjukkan bahwa multimedia interaktif memperoleh kategori sangat layak berdasarkan penilaian para ahli dan respons peserta didik, serta terbukti efektif meningkatkan hasil belajar dengan perbedaan yang signifikan antara kelas eksperimen dan kelas kontrol disertai pengaruh pada kategori sedang. Kebaruan penelitian ini terletak pada pengembangan multimedia interaktif yang mengintegrasikan materi, contoh, latihan bertahap, umpan balik, dan evaluasi dalam satu platform untuk mendukung proses kreatif menciptakan puisi. Temuan ini menunjukkan bahwa multimedia interaktif dapat menjadi alternatif media pembelajaran Bahasa Indonesia yang mendukung pembelajaran lebih aktif, bermakna, dan berorientasi pada peningkatan hasil belajar peserta didik.